A randomized trial of non-fasting vs. fasting for cardiac implantable electronic device procedures (Fast-CIED Study) . Issue 10 (21st June 2022) - Bode, Kerstin; Gerhards, Matthias; Doering, Michael; Lucas, Johannes; Tijssen, Jan; Dagres, Nikolaos; Hilbert, Sebastian; Richter, Sergio; Nedios, Sotirios; Lurz, Julia; Moscoso-Luduena, Cathleen; Arya, Arash; et al.
Abstract: Aims: Data on safety and efficacy of a non-fasting strategy in minimal invasive cardiac procedures are lacking. We assessed a non-fasting strategy compared with a fasting strategy regarding patient's well-being and safety in elective cardiac implantable electronic device (CIED) procedures. Methods and results: In this randomized, single-blinded clinical trial, 201 patients (non-fasting = 100, fasting = 101) with a mean age of 72.0 ± 11.6 years (66.7% male) were assigned to a non-fasting strategy (solids/fluids allowed up to 1 h) or a fasting strategy (at least 6 h no solids and 2 h no fluids) before the procedure and analysed on an intention-to-treat basis. The co-primary outcomes were patients' well-being scores (based on numeric rating scale, 0–10) and incidence of intra-procedural food-related adverse events, including vomiting, perioperative pulmonary aspiration, and emergency intubation. Renal, haematological, and metabolic blood parameters and 30-day follow-up data were gathered. The summed pre-procedural patients' well-being score was significantly lower in the non-fasting group [non-fasting: 13.1 ± 9.6 vs. fasting: 16.5 ± 11.4, 95% confidence interval (CI) of mean difference (MD) −6.35 to −0.46, P  = 0.029], which was mainly driven by significantly lower scores for hunger and tiredness in the non-fasting group (non-fasting vs. fasting; hunger: 0.9 ± 1.9 vs. 3.1 ± 3.2, 95% CI of MD −2.86 to −1.42, P  < 0.001; tiredness: 1.6 ± 2.3 vs. 2.6 ± 2.7, 95% CI of MD −1.68 to −0.29, P  = 0.023). No intra-procedural food-related adverse events were observed. Relevant blood parameters and 30-day follow-up did not show significant differences. Conclusion: These results showed that a non-fasting strategy is beneficial to a fasting one regarding patient's well-being and comparable in terms of safety for CIED procedures (NCT04389697). Graphical Abstract: Graphical Abstract